Functions and Sales Arguments in Spanish Advertising. A Study on Female Representation (2018)
Advertising is responsible for developing part of the contemporary imaginaries, which tend to be imposed as referential frameworks, especially for strategic groups such as those embodied by young people. In this regard, in the following article we present the results of a study in which we evaluated 1520 images published in advertisements from the main Spanish high-end women's magazines (Cosmopolitan, Elle, Glamor, Telva and Vogue). The results in these publications highlight the presence of a restrictive body type for women, which imposes canons of beauty where thinness and slenderness prevail, and to which physical qualities are associated such as white ethnicity, light eyes tonalities, dark or light hair with a length between the shoulders and the chest, a palpable youth and extreme corporal perfection. And also, a pattern that characterizes women devoid of intellectual roles and arguments to purchase and sell, which is an example of symbolic power and objectification of the female body.